Dissociation of Peripheral T Cell Responses from Thymocyte Negative Selection by Weak Agonists Supports a Spare Receptor Model of T Cell Activation - McNeil, Lisa K.; Evavold, Brian D. (Proceedings of the National Academy of Sciences - PNAS, 2002)
We have focused on stability of the peptide-MHC complex as a determining factor of ligand potency for thymocytes and peripheral CD4+T cell responses. MHC variant peptides that have low affinities and fast dissociation rates are different in that they stimulate proliferation and cytolysis of mature T cells (classifying the variant peptides as weak agonists) but do not induce thymocyte negative selection. The MHC variant weak agonists require significant receptor reserve, because decreasing the level of T cell receptor on mature T cells blocks the proliferative response. These results demonstrate that peripheral T cells are more sensitive to MHC variant ligands by virtue of increased T cell receptor expression; in addition, the data support a T cell model of the spare receptor theory.